Predictor Factor for Severity Degree of Pediatric Hydronephrosis in Tertiary Hospital - Hamdan Yuwafi Naim; Besut Daryanto; Pradana Nurhadi (Fakultas Kedokteran Universitas Brawijaya, 2022)
Pediatric hydronephrosis is often hideous, and its severity highly correlates with a significantly increased incidence of pathological condition and outcome. The management of this disease is based on the severity level by identifying the clinical manifestation, so performing an early detection is crucial to prevent the disease progression. This research aimed to determine the predictor factors for the severity degree of pediatric hydronephrosis to give better treatments for patients. This study retrospectively reported 51 data of hydronephrosis cases that were collected from January 2012 to August 2019. Severity degree was evaluated using SFU (Society of Fetal Urology) scoring system and divided into two groups, mild-moderate (first and second degree) and moderate-severe (third and fourth degree). Data including age, gender, number of kidneys affected, etiology, and antenatal care were collected and statistically analyzed using Pearson's Chi-square and Fischer Exact test. The research result from 51 pediatric patients, 72.55% were categorized as moderate-severe hydronephrosis while the remaining 27.45% were categorized ad mild-moderate hydronephrosis. Ureteropelvic junction (UPJ) stenosis (37.25%) is the most common cause of pediatric hydronephrosis. Significant correlations are noted among severity degree and gender, the number of kidneys affected, etiology, and chosen antenatal care between obstetrician-gynecologist and midwife (p<0.05). In short, gender, number of kidneys affected, etiology, patient's choice on antenatal care can be the predictor factors for pediatric hydronephrosis. Thus, these findings are essential for urologists in pediatric hydronephrosis management.